Insights into the Electronic Structure of Fe Penta-Coordinated Complexes. Spectroscopic Examination and Electrochemical Analysis for the Oxygen Reduction and Oxygen Evolution Reactions - Ureta-Zanartu, M; Zagal-Moya, J; Zagal-Moya, J; Aliaga-Vidal, C; Aliaga-Vidal, C; Tasca-Gottardo, F; Tasca-Gottardo, F; Zúñiga-Loyola, C; Zúñiga-Loyola, C (Royal Society of Chemistry, 2021)
Fe phthalocyanine was coordinated to pyridine-modified carbon nanotubes and studied as a catalyst for the oxygen reduction (ORR) and oxygen evolution reactions (OER). X-ray photoelectron spectroscopy (XPS), Mössbauer, and electron paramagnetic resonance spectroscopy (EPR) analysis supported that pyridine acts as an axial ligand to yield penta-coordinated catalytic active Fe sites. The impedance analyses show an increase in the double-layer capacitance (Cdl) value, corroborating the adsorption of the complexes to give FePc-Py-CNT. The evaluation of the electrocatalytic activity for the ORR was performed in both acid (0.1 M H2SO4) and basic (0.1 M KOH) media, while the evaluation of the OER activity was investigated only in alkaline medium. DFT studies revealed an increased length in the Fe-N binding of the pentacoordinate Fe-based site, leading to a decreased O2-Fe binding energy, explaining the higher ORR and OER activity of FePc-Py-CNT relative to FePc-CNT. © The Royal Society of Chemistry 2021.